The European Union’s Policies Towards Iraq (2014–2020) - L. D. Oganisyan (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Political instability in the Middle East and North Africa in the early 2010s, accompanied by an escalation of the terrorist threat and uncontrolled migration, caused serious concern in the European Union about the situation in the Arab world. As a consequence, the EU has noticeably increased assistance to Iraq, providing Baghdad with substantial support in the ﬁght against the Islamic State, preventing the humanitarian crisis, stabilizing the situation and promoting post-conﬂict reconstruction. However, these eﬀorts have not yet been explored in depth by the Russian experts, who traditionally focus on the EU relations with the Southern Mediterranean countries.The author aims to reveal the logic behind the evolution of the European Union’s policy towards Iraq since 2014, as well as its impact on the EU assistance programmes to this country. The paper consists of three sections: the ﬁrst one outlines the evolution of the EU strategic priorities in Iraq during 2014–2019, the second covers the major assistance programmes implemented by the European Union, both bilaterally and multilaterally, in Iraq; the third examines the EU reaction to the rising tensions in Iraq at the turn of 2019–2020.The author concludes that the EU’s growing interest in Iraq in recent years stems not only from concerns about transformation of this country into a source of cross-border challenges and threats, but also from the conviction of the EU oﬃcials that Iraq might potentially become the cornerstone of a new regional security architecture. On the basis of these considerations, the EU provides a comprehensive support to Iraq, including both humanitarian aid and development assistance aimed primarily at eliminating the fundamental causes of instability and radicalization. At the same time while demonstrating its commitment to develop cooperation with both government agencies and non-governmental organizations, the EU clearly prefers to assist Iraq through international organizations, rather than directly. Although the EU’s ability to inﬂuence Baghdad remains limited, compared to that of the US and regional actors, the European Union is perceived in Iraq as a neutral player and this might facilitate the achievement of its policy objectives. However, taking into account such factors as a high level of corruption in Iraq, substantial resources for reconstruction already available for the country, as well as Brussels’ focus on Syria, the scope of the EU’s further involvement in Iraq remains unclear.